Jamieson's dictionary of Scots : the story of the first historical dictionary of the Scots language - Rennie, Susan, 1962-; Jamieson, John, 1759-1838. (Oxford : Oxford University Press, 2012)
An account of the making of John Jamieson's pioneering 'Etymological Dictionary of the Scottish Language'. Susan Rennie describes Jamieson's work and methods, interweaving her account with biography and linguistic, social, and book history to present a rounded picture of the man, his work, and his times.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Keywords: Jamieson, John, -- 1759-1838.; Scots language -- History